The Relevance of the Concept of Islamic Education in Ibnu Khladun's Perspective in the Contemporary Era - Rofiqoh, Nihayatur; Bakar, M Yunus Abu (research, training and philanthropy institution Natural Aceh, 2025)
This research aims to discover how Ibn Khaldun views the concept of Islamic education, the educational process, and its relevance to contemporary Islamic education. The method used in this research is a literature study (Library Research) using a descriptive qualitative approach. The researcher seeks to collect data through several books, articles, journals, or other sources related to Ibn Khaldun's Islamic education thought. The researcher analyzes it and explores significant aspects related to the relevance of Ibn Khaldun's Islamic education. This research results in Ibn Khaldun's concept of education, which is neatly designed and holistic and helps human development. Ibn Khaldun's concept of education provides a philosophical foundation for education that integrates traditional values with modern needs. The principles put forward by Ibn Khaldun are still relevant in the contemporary era, especially in the use of technology or learning media. The concept of education, from Ibn Khaldun's perspective, can build an adaptive system, producing intelligent individuals who have integrity and are ready to contribute to the progress of civilization. Likewise, the role of the teacher is to be a means of learning transformation and to assist in shaping the identity of students. This meets modern civilization's needs and integrates traditional and innovative values.